Defining the Contribution of Adipocyte Subpopulations to Dermal White Adipose Tissue - Leyendecker, Mara (J Endocr Soc, 2021)
Introduction: Our lab has previously identified three distinct subtypes of developmentally and functionally white adipocytes and have shown that they each differentially contribute to adipose depots (Lee, KY et al. EMBO J. 2019). Dermal white adipose tissue (dWAT), a layer of adipocytes embedded in the skin below the dermis, has recently been shown to play a role in crucial physiologic processes including thermogenesis, the regulation of aging, scar formation, and wound healing. The purpose of this proposal is to investigate the contribution of three adipocyte subtypes to dWAT. Objectives: The primary objectives of this project are to determine the number of preadipocytes and adipocytes from each of three subtypes present in dWAT. Methodology: Lineage tracing analysis was performed by crossing transgenic mice harboring cre-recombinase under the control of promoter/enhancer elements of each of the three marker genes, Wilms tumor 1, transgelin, or myoxovirus 1 to dual- fluorescent reporter mice. These three mice lines mark Type 1–3 preadipocytes and adipocytes, respectively. dWAT was collected from X week old mice, and adipocyte identities were determined by confocal microscopy. Preadipocyte contribution of these subpopulations was determined by FACS analysis. Results: We found that Type 2 (~45%) and Type 3 (~25%), but not Type 1 preadipocytes significantly contributed to the dWAT preadipocyte cellular population. We also found a similar pattern for the adipocyte populations. Type 1, 2, and 3 adipocytes were found to comprise ~3%, 17%, and 7% of mature adipocytes, respectively. These studies demonstrate that Type 2 and Type 3 adipocytes contribute to the composition of dWAT. Summary/Conclusion: These studies demonstrate that Type 2 and Type 3 adipocytes and preadipocytes significantly contribute to the composition of dWAT. Since these adipocyte subpopulations have different functional properties, including metabolism and response to inflammatory cytokines, the contribution of these adipocyte subtypes may impact the crucial physiologic processes mediated by dWAT.